2016
DOI: 10.3762/bjoc.12.230
|View full text |Cite
|
Sign up to set email alerts
|

Efficient mechanochemical synthesis of regioselective persubstituted cyclodextrins

Abstract: A number of per-6-substituted cyclodextrin derivative syntheses have been effectively carried out in a planetary ball mill under solvent-free conditions. The preparation of Bridion® and important per-6-amino/thiocyclodextrin intermediates without polar aprotic solvents, a source of byproducts and persistent impurities, could be performed. Isolation and purification processes could also be simplified. Considerably lower alkylthiol/halide ratio were necessary to reach the complete reaction in comparison with thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…Recently, focus has been in controlling selectivity of organic reactions under solventless ball‐milling conditions . Concurrently with works of Cravotto et al., we showed that regioselective mono‐2‐ O ‐tosylation of the secondary face of CDs proceeds quantitatively upon grinding on very short reaction times (ca. 1 min) via supramolecular means, the reactant (tosylimidazole) being included into the CD cavity .…”
Section: Figuresupporting
confidence: 76%
“…Recently, focus has been in controlling selectivity of organic reactions under solventless ball‐milling conditions . Concurrently with works of Cravotto et al., we showed that regioselective mono‐2‐ O ‐tosylation of the secondary face of CDs proceeds quantitatively upon grinding on very short reaction times (ca. 1 min) via supramolecular means, the reactant (tosylimidazole) being included into the CD cavity .…”
Section: Figuresupporting
confidence: 76%
“…[9][10][11][12][13] However,t he substrate preorganization in hydroformylation reactions could also be achieved through hydrophobic effects.F or example,w es howed that bidentate ligands and cyclodextrins (CDs,c yclic oligosaccharides consisting of glucopyranose units) supramolecularly interact to compel terminal alkenes to react preferentially by their terminal carbon, leading to very high regioselectivity toward linear aldehyde. [15] Concurrently with works of Cravotto et al, [16,17] we showed that regioselective mono-2-O-tosylation of the secondary face of CDs proceeds quantitatively upon grinding on very short reaction times (ca. [15] Concurrently with works of Cravotto et al, [16,17] we showed that regioselective mono-2-O-tosylation of the secondary face of CDs proceeds quantitatively upon grinding on very short reaction times (ca.…”
supporting
confidence: 64%
“…The NMR experiments were carried out on 2 Bruker AVANCE spectrometers (400 and 600 MHz). They were therefore performed respectively at 400 MHz for 1 H and 101 MHz for 13 C, or 600 MHz for 1 H and 151 MHz for 13 C. The deuterated solvents used were pyridine, chloroform, water, or methanol.…”
Section: Nmr Analysismentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 ) δ (ppm): 3.65 (s, 3H, OCH 3 ), 2.96-2.82 (m, 2H, H 9 and H 10 ), 2.31-2.27 (t, 2H, J = 7.5 Hz, CH 2 COOCH3), 1.71-1.55 (m, 2H, CH 2 ), 1.55-0.96 (m, 24H, CH 2 ), 0.87 (t, 3H, J = 6.9 Hz, CH 3 ). 13 C NMR (101 MHz, CDCl 3 ) δ (ppm): 174.4 (C=O), 57.4, 57.3 (C-9 and C-10), 51.6 (C-…”
Section: Methyl Oleate Epoxidementioning
confidence: 99%
See 1 more Smart Citation